2010
DOI: 10.1007/s00540-009-0845-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphine enhances tissue content of collagen and increases wound tensile strength

Abstract: Purpose Morphine is a commonly prescribed analgesic for wound pain. Previous studies have shown that morphine enhances accumulation of collagen in cultured fibroblasts. Because fibroblasts are important for the remodeling of connective tissue in incisional wound, this study investigates the biological effects of morphine on cutaneous collagen content and wound tensile strength. Methods A full-thickness incisional wound (2 cm in length) was created on the dorsum of mice followed by treatment with placebo or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
(39 reference statements)
2
20
0
1
Order By: Relevance
“…71,8084 The relationship between mechanical stress and collagen dynamics can have negative implications for scar formation. 21,50,58,87,88 This is supported by the increased incidence of abnormal scar formation in areas subject to the most movement, such as the scapular region and chest. 69,89,90 Minimization of movement over these areas has been shown to reduce the degree of abnormal scarring.…”
Section: Mechanical Stress and Scarringmentioning
confidence: 95%
See 1 more Smart Citation
“…71,8084 The relationship between mechanical stress and collagen dynamics can have negative implications for scar formation. 21,50,58,87,88 This is supported by the increased incidence of abnormal scar formation in areas subject to the most movement, such as the scapular region and chest. 69,89,90 Minimization of movement over these areas has been shown to reduce the degree of abnormal scarring.…”
Section: Mechanical Stress and Scarringmentioning
confidence: 95%
“…35,40,42,45,50 This step improves the tensile strength of incisional wounds because the fibers bind to cell-membrane proteins across the wound interface. 51,52 The fibers, therefore, act as a bridge between the 2 wound edges and provide significant resistance to tensile force (Fig.…”
Section: Physiology Of the Wound-healing Trajectorymentioning
confidence: 99%
“…The α‐5 fraction of type IV collagen plays an important role in corneal transparency 26 . Recent data demonstrated that systemic administration of morphine enhances tissue types I–IV collagen deposition in the cutaneous tissue, increasing tensile strength of the incisional wound 27 …”
Section: Introductionmentioning
confidence: 99%
“…Healing of a surgical incision is mainly dependent on the tissue collagen deposition (Chang et al 2010). A major element of healing in suture-closed wounds is the integration of newly deposited collagen with the residual dermal collagen fibers at the edges of the wound; therefore collagen contributes a lot to the restoration of wound strength.…”
mentioning
confidence: 99%